Molecular evolutionary analysis of the SHI/STY gene family in land plants: A focus on the Brassica species - Fang, Da; Zhang, Weimeng; Cheng, Xiuzhu; Hu, Fei; Ye, Ziyi; Cao, Jun (Frontiers in Plant Science, 2022)
Abstract The plant-specific SHORT INTERNODES/STYLISH (SHI/STY) proteins belong to a family of transcription factors that are involved in the formation and development of early lateral roots. However, the molecular evolution of this family is rarely reported. Here, a total of 195 SHI/STY genes were identified in 21 terrestrial plants, and the Brassica species is the focus of our research. Their physicochemical properties, chromosome location and duplication, motif distribution, exon-intron structures, genetic evolution, and expression patterns were systematically analyzed. These genes are divided into four clades (Clade 1/2/3/4) based on phylogenetic analysis. Motif distribution and gene structure are similar in each clade. SHI/STY proteins are localized in the nucleus by the prediction of subcellular localization. Collinearity analysis indicates that the SHI/STYs are relatively conserved in evolution. Whole-genome duplication (WGD) is the main factor for their expansion. SHI/STYs have undergone intense purifying selection, but several positive selection sites are also identified. Most promoters of SHI/STY genes contain different types of cis-elements, such as light, stress, and hormone-responsive elements, suggesting that they may be involved in many biological processes. Protein-protein interaction predicted some important SHI/STY interacting proteins, such as LPAT4, MBOATs, PPR, and UBQ3. In addition, the RNA-seq and qRT-PCR analysis were studied in detail in rape. As a result, SHI/STYs are highly expressed in root and bud, and can be affected by Sclerotinia sclerotiorum, drought, cold, and heat stresses. Moreover, quantitative real-time PCR (qRT-PCR) analyses indicates that expression levels of BnSHI/STYs are significantly altered in different treatments (cold, salt, drought, IAA, auxin; ABA, abscisic acid; 6-BA, cytokinin). It provides a new understanding of the evolution and expansion of the SHI/STY family in land plants and lays a foundation for further research on their functions.